An unusual case of colonic intussusception in old age. Issue 2 (April 2019) - Alshoabi, Sultan A.; Abdulaal, Osamah M.
الخلاصة: الانغلاف المعوي هو دخول جزء من الأمعاء الى الجزء المجاور منها وهو سبب نادر لانسداد الأمعاء عند الكبار. عادة ياتي المريض وفيه علامات البطن الحاد الذي يشمل مجموعة واسعة من الحلات الطارئة. على الرغم انه من الصعب تشخيص الانغلاف سريريا الا انه من السهل تشخيصه عن طريق التصوير الطبي. التصوير بالموجات فوق الصوتية والتصوير المقطعي المحوسب يمكنه بسهولة اكتشاف الانغلاف المعوي. هذا التقرير يصف موقع غير معتاد لانغلاف القولون عند مريض عمره سبعين عاما. كل من عمر المريض ومكان هذه الحالة امر نادر الحدوث. Abstract: Intussusception refers to the telescoping of a bowel segment into the lumen of an adjacent distal bowel. It is a rare entity and an uncommon cause of intestinal obstruction in adults. Approximately 90% of cases of intussusception in adults have an organic cause as a lead point. Usually, the patient presents with signs of acute abdomen with a short history. Although it is difficult to diagnose colonic intussusception clinically, medical imaging by ultrasonography and computed tomography can easily detect this rare but clinically important disease. This case report describes an uncommon location of intussusception in the colon in a 70-year-old female patient.